Fabrication and characterization of medium‐entropy carbide ceramics in low temperature sintering. Issue 3 (14th December 2022) - Zou, Qin; Li, Zhuang; Li, Yanguo; Li, Shuang; Gu, Haotian; He, Wenquan; Luo, Yongan
Abstract: The medium‐entropy carbide (W, Ti, V)C0.8 ceramics were prepared by sparking plasma sintering at temperatures between 1400 and 1700°C. The effects of sintering temperature on the microstructure and mechanical properties of the medium‐entropy carbide (W, Ti, V)C0.8 ceramics were investigated. X‐ray diffraction, scanning electron microscope, and energy dispersive spectrometer were used to confirm the formation of single‐phase face‐centered cubic (FCC) solid solution of the medium‐entropy carbide (W, Ti, V)C0.8 ceramics prepared at a sintering temperature of 1600°C. It was found that the mechanical properties of the material were improved by solid solution strengthening during the formation of single‐phase FCC solid solution, and the best overall performance of the medium‐entropy carbide (W, Ti, V)C0.8 ceramics was achieved at 1600°C, when the hardness value was 22.3 ± 1.8 GPa, the fracture toughness was 5.7 ± 0.8 MPa·m 1/2, the flexural strength was 605 ± 4 MPa, and the compressive strength was 1.84 GPa. Most importantly, the addition of TiC0.4 promoted the diffusion among the elements of the medium‐entropy carbide (W, Ti, V)C0.8 ceramics, which contributed to the formation of single‐phase FCC solid solution and significantly reduced the sintering temperature of the medium‐entropy carbide (W, Ti, V)C0.8 ceramics due to the effect of vacancies. This study provides a new idea for the preparation of medium‐entropy carbide ceramics.